Empowering Faculty: Advancing Pedagogical Training and Support for Digital Teaching - Enciso-Huamani, Edith; Iparraguirre, Régulo Pastor Antezana; Javier-Eduardo, Huaynate-Hidalgo; Soto, Fidel Chocce; Crispin, Hobet Meneses; Castillo, Carlos Eduardo Lazo; Ccama, Juan Carlos Huarcaya; Cépida, Raúl Alexander Quispe; Leon, José Ramos; Loayza, Juan Zevallos; Molina, Jacqueline Denisse Llacza; Paquiyauri, Pablo Rojas (Journal of Posthumanism, 2025)
The study explored the impact of the COVID-19 pandemic on undergraduate students at National University of Huancavelica, Peru, focusing on their use of academic resources. A structured questionnaire was distributed to 1,291 students, selected through random sampling stratified. The research revealed that 77.9% of students rated academic service delivery negatively, particularly those in rural areas with limited internet and technology access. Engineering and Agricultural Sciences students had the lowest evaluations. The study employed statistical methods, including Chi-Square tests and One-Way ANOVA, confirming significant relationships between technology access, demographics, and student perceptions. The findings highlight the need for improved digital infrastructure, expanded internet access, and faculty support to ensure equitable learning opportunities. The pandemic underscored the necessity for resilient, uniform academic support systems to address the disparities in service delivery across all student populations, regardless of technical limitations.